Pembuatan Selai Salak (Salacca edulis reinw) : Kajian Dari Penambahan Natrium Benzoat Dan Gula Yang Tepat Terhadap Mutu Selai Salak Selama Penyimpanan (Jurnal Teknologi Pangan, 2013)
This research aimed to define a proper concentration of preservative and sugar added for “selai salak” storage-life. This research used random block design which was containing two factors treatment with three (3) times repeating. First factor was the concentration of preservative (A1 = 0%, A2 = 0,05% and A3 = 0,1%). Second factor was concentration of sugar (B1 = 55% and  B2 = 75%. It will be analysed at first day and 30th day. The parameters would be analysed were water contain and sum micro-organism, also hedonic test.    The result showed that the best alternative processing of A1B2 (0%  natrium benzoat and 75% sugar) with pay off 21,91 based on product quality (water contain, sum micro-organism and hedonic test).Key words: ‘selai salak’, preservative, polyethylene, polypropylene and vacuum